Assessment of the financial management and financial sustainability of the capitation system of The National Health Insurance Scheme in the Ashanti Region, Ghana - Dei-Kwarteng, Afia (2016)
Thesis submitted to the department of accounting and finance, Kwame Nkrumah University of Science and technology in partial fulfillment of the requirement for the degree of Master of Business Administration (finance option),